2003
DOI: 10.1073/pnas.2133253100
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of 5-lipoxygenase as a determinant of leukotriene B4synthetic capacity

Abstract: The enzyme 5-lipoxygenase (5-LO) initiates the synthesis of leukotrienes from arachidonic acid. In resting cells, 5-LO can accumulate in either the cytoplasm or the nucleoplasm and, upon cell stimulation, translocates to membranes to initiate leukotriene synthesis. Here, we used mutants of 5-LO with altered subcellular localization to assess the role that nuclear positioning plays in determining leukotriene B4 (LTB4) synthesis. Mutation of either a nuclear localization sequence or a phosphorylation site reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 42 publications
3
110
0
Order By: Relevance
“…Phosphorylation of 5-LOX at Ser271 by the P38-activated kinase mitogen-activated protein kinase-activated protein kinase 2 (MAPKAPK2) (MK2) leads to nuclear localization of 5-LOX, which allows 5-LOX to align with other enzymes required for LTB 4 synthesis (17,(23)(24)(25). We found that RvD1 blocked AA-stimulated phosphorylation of both kinases, which is a measure of their activation state ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Phosphorylation of 5-LOX at Ser271 by the P38-activated kinase mitogen-activated protein kinase-activated protein kinase 2 (MAPKAPK2) (MK2) leads to nuclear localization of 5-LOX, which allows 5-LOX to align with other enzymes required for LTB 4 synthesis (17,(23)(24)(25). We found that RvD1 blocked AA-stimulated phosphorylation of both kinases, which is a measure of their activation state ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Plasmids, Mutagenesis, and DNA Construction-Plasmids containing the wild type (WT) 5-LO and the S523A and the S271A mutants of 5-LO alone in pcDNA or fused to green fluorescent protein (GFP) in pEGFP have been described previously (34,36,46). Substitutions of Leu-270 and Leu-272 with Ala in 5-LO were performed using the QuikChange site-directed mutagenesis kit (Stratagene, La Jolla, CA) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…4B). Importantly, NIH 3T3 cells overexpressing S271A 5-LO produce significantly less than half as much LTB 4 when stimulated with calcium ionophore (10 M) with added arachidonic acid (10 M) versus cells with WT 5-LO (1912 ϩ 232 versus 4570 ϩ 807 pg/ml; p Ͻ 0.01) (34). Treatment of NIH 3T3 cells expressing S271A 5-LO with the nuclear export inhibitor lmb (5 ng/ml, 2 h) resulted in the redistribution of 5-LO to the nucleus (Fig.…”
Section: Ser-271 Is Phosphorylated On 5-lo In Untreated Nih 3t3mentioning
confidence: 96%
See 1 more Smart Citation
“…It is clear that not only the supply of AA but also the access towards 5-LO is a prerequisite for LT biosynthesis [44], [45], and one important class of synthetic inhibitors of LT biosynthesis are so-called FLAP inhibitors (e. g., MK-886, Bay-X-1005). Among plant-derived compounds, the phenylanthraquinone knipholone 54 ( Table 3), from the roots of Kniphofia foliosa, was suggested to suppress cellular 5-LO product synthesis by inhibition of FLAP [46].…”
mentioning
confidence: 99%